‘The tabernacle of David that is fallen’ (Am 9:11): An Exegetical Study of a Moot Expression - Coniglio, Alessandro (Liber Annuus, 2013)
Abstract Am 9:11-15 is an oracle of consolation. It is often regarded as an addition to the original prophecies because it speaks about a messianic hope of Davidic restoration in a book which is centered on the Northern Kingdom of Israel. This study will be limited to the first expression of the oracle, in particular to the mention of the “Fallen Tabernacle of David”. It is my opinion that the Sukkat David should be read in the context of the rich imagery of buildings in the book of Amos. Thus it appears clear that it is not important to identify what is meant by the prophet (either Jerusalem, or the Temple, or the Davidic Dynasty, etc.). Rather it is more important to understand the metaphor of the temporary and frail structure (a booth) of David in opposition to the stable and firm buildings of the countries around Judah (the pagan nations of Amos 1, together with Samaria throughout the Book): fortresses, temples, houses, and so on.